2017
DOI: 10.1016/j.biomaterials.2017.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Selective laser sintering scaffold with hierarchical architecture and gradient composition for osteochondral repair in rabbits

Abstract: Osteochondral defects cannot be adequately self-repaired due to the presence of the sophisticated hierarchical structure and the lack of blood supply in cartilage. Thus, one of the major challenges remaining in this field is the structural design of a biomimetic scaffold that satisfies the specific requirements for osteochondral repair. To address this hurdle, a bio-inspired multilayer osteochondral scaffold that consisted of the poly(ε-caprolactone) (PCL) and the hydroxyapatite (HA)/PCL microspheres, was cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
212
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(213 citation statements)
references
References 54 publications
(58 reference statements)
0
212
1
Order By: Relevance
“…When the pore sizes were small, the permeation rate of buffer solution into the scaffolds was slow, leading the low DRs. These results indicated that the catechol modification could effectively adjust the degradation of the scaffolds to be satisfied with the bone or cartilage regeneration …”
Section: Results and Disscussionmentioning
confidence: 82%
“…When the pore sizes were small, the permeation rate of buffer solution into the scaffolds was slow, leading the low DRs. These results indicated that the catechol modification could effectively adjust the degradation of the scaffolds to be satisfied with the bone or cartilage regeneration …”
Section: Results and Disscussionmentioning
confidence: 82%
“…Using selective laser sintering, several bone compatible scaffolds have been printed (Du et al, ). With its unprecedented resolution and high precision, laser‐assisted bioprinting has been applied to in situ printing.…”
Section: Bioprinting Technologiesmentioning
confidence: 99%
“…In this study, biodegradation behavior of the Alg-DA/QCHA gradient scaffolds was detected in a simulated body fluid (SBF) for five weeks, as shown in Figure 4. 22,29 In vitro biomineralization behavior of Alg-DA/QCHA gradient scaffolds Natural bone is an inorganic-organic complex composed of HA and macromolecular collagen fibers. The bottom layer with high QCHA composition displayed a quicker degradation, compared to the other layers with lower QCHA compositions.…”
Section: Synthesis and Characterization Of Qchamentioning
confidence: 99%